Implementasi Lingkungan Test pada Moodle dengan Apache JMeter - Kurnia Ade Prasetia; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Moodle provides convenience in the teaching and learning process in this modern era. Starting from learning material, working on tests, uploading files can be done easily. Apart from the convenience provided and the increasing number of teaching and learning processes using Moodle, the burden on the Moodle server will also be greater. Apache jMeter provides tools for monitoring and testing performance. With a simple GUI, its use is not difficult to learn. In this research, we tested the moodle server with the PostgreSQL database installed in virtualbox. Then a performance test was carried out through Apache jMeter which included a CPU performance test, Disk I/O performance test, and a memory performance test on the login page and quiz submit page. The simulation was carried out in stages starting from one repetition, ten repetitions, fifty repetitions, and one hundred repetitions. From the test results it was found that the test results showed the same results because they were carried out in the same session at the same time